2022
DOI: 10.1037/dhe0000281
|View full text |Cite
|
Sign up to set email alerts
|

Space and place at Asian American and Pacific Islander–serving community colleges: The geography of campus student support for Asian American and Pacific Islander students.

Abstract: This study examines the perceived changes in the geography of student support for racial/ethnic minoritized students after pursuing federal Minority-Serving Institution (MSI) designation and grants. Specifically, this qualitative multiple-case study examines the decision-making related to, and perceived changes in, space and place aimed at supporting Asian American and Pacific Islander (AAPI) students at three AAPI-serving community colleges. The three themes related to changes in the geography of student supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…The authors highlight that these campus artifacts are "a daily reminder of historical trauma and erasure" (p. 285) that contribute to Native students' marginalization. Another study highlighted institutional agents' critical role in developing campus artifacts for AAPIs at AANAPISIs (Alcantar et al, 2020). Our study extends this literature by locating this phenomenon within dually designated AANAPISI-HSIs.…”
Section: Conceptual Frameworksupporting
confidence: 69%
See 1 more Smart Citation
“…The authors highlight that these campus artifacts are "a daily reminder of historical trauma and erasure" (p. 285) that contribute to Native students' marginalization. Another study highlighted institutional agents' critical role in developing campus artifacts for AAPIs at AANAPISIs (Alcantar et al, 2020). Our study extends this literature by locating this phenomenon within dually designated AANAPISI-HSIs.…”
Section: Conceptual Frameworksupporting
confidence: 69%
“…Campus artifacts include artwork (e.g., murals, statuary), signage (i.e., building names), graffiti, and architecture (e.g., buildings;Banning et al, 2008). The authors expand the conception of campus artifacts by including digital platforms (Torres & Zerquera, 2012) and a campus' geography (Alcantar et al, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Although this is a practice often promoted in student affairs generally, finding and working with allies were critically important for AANAPISI PDs, specifically, because the purpose of the program is student success, an outcome shaped by a variety of touch points across the institution that can be undergirded by collaboration (Kezar, 2001a). And finally, embedding the program within existing institutional structures, such as longstanding events or organizations, offered strategic opportunities and possibilities for the PDs to sustain their programs (Alcantar et al, 2020). By integrating the AANAPISI into more well-established initiatives, it gave the AANAPISI program gravitas among faculty and institutional leaders, allowing the PDs to use this platform to promote buy-in, secure partnerships, and resources.…”
Section: Discussionmentioning
confidence: 99%
“…While not within the community college context, there are several studies that revealed how imagery, visual representation, and physical artifacts impact students' belonging (Alcantar et al, 2022(Alcantar et al, , 2020 This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Visual Mediums' Impact On Lgbtqia+ Students' Identity Develo...mentioning
confidence: 99%